2010
DOI: 10.3238/arztebl.2010.0123
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Impairment and Its Effects on Quality of Life in Patients With Rectal Cancer

Abstract: These findings show that the quality of life is changed by surgery for rectal cancer and is influenced by the patient's sex and age, as well as by the particular surgical approach used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…34 in addition, an increased risk of surgical damage to the pelvic autonomic nerves contributes to the morbidity associated with this technique, as avulsion of the pelvic splanchnic nerves from their sacral roots is likely to occur following an inadvertent tear of the presacral parietal fascia during the perineal phase of the procedure. 13,43,54,55 Pelvic lymph node dissection the addition of extended pelvic lymph node dissection to simple tumor resection adversely influences urinary and sexual function. in western countries this procedure is sometimes added to surgical resection in patients with metastatic disease.…”
Section: Ihpmentioning
confidence: 99%
“…34 in addition, an increased risk of surgical damage to the pelvic autonomic nerves contributes to the morbidity associated with this technique, as avulsion of the pelvic splanchnic nerves from their sacral roots is likely to occur following an inadvertent tear of the presacral parietal fascia during the perineal phase of the procedure. 13,43,54,55 Pelvic lymph node dissection the addition of extended pelvic lymph node dissection to simple tumor resection adversely influences urinary and sexual function. in western countries this procedure is sometimes added to surgical resection in patients with metastatic disease.…”
Section: Ihpmentioning
confidence: 99%
“…[4, 11] Those who remain active, however, report high rates of symptoms associated with vulvovaginal atrophy, such as dryness and pain with sex (dyspareunia), as well as problems like vaginal stenosis, loss of sexual desire, and interference with sex from fecal incontinence. [4-6, 20] Rates of female sexual problems, especially dyspareunia, are higher after APR than other types of anterior resection (AR),[6, 25, 26] and are also increased in women who have adjuvant radiotherapy. [6, 9, 10, 19]…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of studies investigating HRQoL and sexual function comparing abdominoperinal extirpation and low anterior resection without permanent colostomy. Some studies report a comparable HRQoL in both operations [5,6] while other studies have found a better HRQoL or sexual function in sphincter preserving operations [7][8][9]. Interestingly, in these latter studies, sphincter preservation or improved anorectal function did not necessarily translate into an improved quality of life [5,6], and a meta-analysis by Pachler et al failed to demonstrate the superiority of sphincter preservation on HRQoL after rectal resection [10].…”
Section: Introductionmentioning
confidence: 89%